Ecotourism as an alternative to traditional tourism (Saoura region model) L’écotourisme comme alternative au tourisme traditionnel (La région de Saoura comme modèle) - NEFFAH, Zakarya; BAHOUSSI, Medjdoub (Finance and Business Economies Review, 2019)
Abstract: The tourism sector has achieved a great level of development and activity, because of several factors such as the rising of income level, standard of living, political stability and security .... etc. On the other hand this development contribute to damage of the environment , in this regard, Philip Kotler said that one of the most important social welfare threats is The polloution. For that the eco-tourism was an alternative to traditional tourism, It‟s a Responsible travel to natural areas that conserves the environment and improves the well-being of local people. Based on that, this paper aims to clarify the basics and elements of eco-tourism with reference to a model of eco-tourism in Algeria (Saoura area).